2023
DOI: 10.31616/asj.2022.0198
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Combined Anesthetic Technique to Improve the Surgical Working Conditions of Lumbar and Thoracolumbar Spine Surgery from a Spine Surgeon’s Perspective: A Prospective Randomized Controlled Study

Abstract: Prospective randomized controlled study. Purpose: This study aimed to assess the effects of a different combination of anesthetic techniques in lumbar and thoracolumbar spinal surgeries in terms of muscle relaxation and surgical field in addition to hemodynamic parameters. Overview of Literature: Adequate relaxation of the erector spinae muscle and good surgical fields are preferred in lumbar spine surgeries. The effects of anesthetic techniques on these parameters have not been evaluated from a surgeon's pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Subbiah et al [ 9 ] and Goel et al [ 36 ], revealed that ESPB was able to reduce the amount of intraoperative muscarinic medication in open thoracolumbar spine surgery, interpreted as relieving tension in the ESM. The current study similarly found a significant reduction in the number of intraoperative myosin additions and the amount of additions in the ESPB group; however, there was no difference in the total amount of intraoperative myosin between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subbiah et al [ 9 ] and Goel et al [ 36 ], revealed that ESPB was able to reduce the amount of intraoperative muscarinic medication in open thoracolumbar spine surgery, interpreted as relieving tension in the ESM. The current study similarly found a significant reduction in the number of intraoperative myosin additions and the amount of additions in the ESPB group; however, there was no difference in the total amount of intraoperative myosin between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, analgesia for lumbar spine surgery was limited to lumbar anesthesia, epidural anesthesia, and local infiltration anesthesia; however, their respective drawbacks limited their application. Although lumbar anesthesia and epidural can provide excellent analgesia, they can produce sympathetic or motor block, thereby affecting the judgement of postoperative neurological function [ 9 ]. Local infiltration anesthesia, the utilization of large amounts of drugs, and limited range, for superficial tissue pain control can be, for deep operation pain control is not effective [ 10 ].…”
Section: Introductionmentioning
confidence: 99%